ANALISIS PENGARUH DIKLAT AUDIT INVESTIGATIF TERHADAP PENINGKATAN KOMPETENSI AUDITOR PEMERINTAH PUSAT DAN DAERAH PADA PUSDIKLATWAS BPKP CIAWI- BOGOR - Budiman Slamet (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
The role of human resources is very important and major in an organization followed by adjustments to the progress of science and technology, where HR is required to have increased competence. HR is needed who can carry out their duties to achieve organizational goals. Needed directed and planned efforts in the development of human resources, by conducting training (training), education programs in accordance with work programs. There are two types of training programs conducted by the BPKP Training Center, namely the JFA Certification Office (Auditor Functional Position) and the Substantive Technical Training (for example: Investigative Audit Training). The Investigative Audit Training conducted by the BPKP Pusdiklatwas can be carried out independently (PNBP) in the sense of being borne by the Agency sending the participants, or fully borne by the BPKP Pusdiklatwas. This study aims to determine the training participants 'perceptions as well as direct training participants' supervisors on the implementation of investigative audit training and analyze their effects on improving the competence of training participants. Indicators of Education and Training are Conformity with Assignments, Teaching Methods, Lecturers / Instructors, Classroom Facilities, and Training Materials. While competency indicators are Knowledge, Skills, Collaboration, Motivation and Responsibility. The type of data collected in this study consists of primary and secondary data. Data analysis and techniques were performed with regression analysis using SPSS 17.0 software. This study argues that organizing an investigative audit training helps auditors in carrying out the technical implementation of an investigative audit in accordance with the work program of each Central / Regional Inspectorate, as well as increasing competence and developing the profession as an auditor. Training participants 'perceptions as well as direct training participants' conclusions gave the conclusion that, the implementation of investigative training had a real effect on increasing the competence of the Ministry / Institution / Regional Inspectorate auditors. Keywords: Investigative Audit Training; Competency Enhancement Auditor